Life, death, and moral order in Sanghyang Siksa Kandang Karesian: An old Sundanese perspective on eschatological consciousness - I Made Dian Saputra; Heri Purwanto; Amarjiva Lochan (Life and Death: Journal of Eschatology, 2026)
Background: This article examines Sanghyang Siksa Kandang Karesian (SSSK) as an Old Sundanese ethical text that explores the relationship between life, death, and moral order. Unlike eschatological understandings that emphasize only the doctrine of the afterlife, this article interprets the eschatological consciousness in the manuscript as a moral framework that operates through teachings on mindfulness, self-control, social order, and the consequences of actions. Methods: Using a qualitative-hermeneutic approach, the data is analyzed through an examination of the moral teachings of SSKK and research reports on the discourse of religious moderation within the text. Findings: The findings indicate that SSKK constructs an eschatological perspective through four key themes; consciousness as the foundation of salvation, life as the arena for the fulfillment of dharma, social order as the guardian of harmony, and non-violence as the prerequisite for the preservation of human dignity. Conclusion: Textual evidence regarding the “guru nista” and “catur buta” demonstrates that death is not positioned merely as a biological event, but as the point at which the moral quality of human life receives its consequence. Novelty/Originality of this article: Thus, SSKK can be read as a model of Nusantara ethical eschatology: not a doctrinal system regarding the afterlife, but a moral pedagogy that positions righteous living as the path toward social and spiritual salvation.